Quantitative T1‐mapping detects cloudy‐enhancing tumor compartments predicting outcome of patients with glioblastoma. (28th November 2016) - Müller, Andreas; Jurcoane, Alina; Kebir, Sied; Ditter, Philip; Schrader, Felix; Herrlinger, Ulrich; Tzaridis, Theophilos; Mädler, Burkhard; Schild, Hans H.; Glas, Martin; Hattingen, Elke
Abstract: Contrast enhancement of glioblastomas (GBM) is caused by the decrease in relaxation time, T1. Here, we demonstrate that the quantitative measurement of T1 (qT1) discovers a subtle enhancement in GBM patients that is invisible in standard MRI. We assessed the volume change of this "cloudy" enhancement during radio‐chemotherapy and its impact on patients' progression‐free survival (PFS). We enrolled 18 GBM patients in this observational, prospective cohort study and measured 3T‐MRI pre‐ and post contrast agent with standard T1‐weighted (T1w) and with sequences to quantify T1 before radiation, and at 6‐week intervals during radio‐chemotherapy. We measured contrast enhancement by subtracting pre from post contrast contrast images, yielding relative signal increase ∆T1w and relative T1 shortening ∆qT1. On ∆qT1, we identified a solid and a cloudy‐enhancing compartment and evaluated the impact of their therapy‐related volume change upon PFS. In ∆qT1 maps cloudy‐enhancing compartments were found in all but two patients at baseline and in all patients during therapy. The qT1 decrease in the cloudy‐enhancing compartment post contrast was 21.64% versus 1.96% in the contralateral control tissue ( P  < 0.001). It was located at the margin of solid enhancement which was also seen on T1w. In contrast, the cloudy‐enhancing compartment was visually undetectable on ∆T1w. A volume decrease of more than 21.4% of the cloudy‐enhancing compartment at first follow‐up predicted longer PFS ( P  = 0.038). Cloudy‐enhancing compartment outside the solid contrast‐enhancing area of GBM is a new observation which is only visually detectable with qT1‐mapping and may represent tumor infiltration. Its early volume decrease predicts a longer PFS in GBM patients during standard radio‐chemotherapy. Abstract : Quantitative T1 subtraction maps uncover a cloudy‐enhancing compartment that is not detected in conventional MRI and has prognostic value for patients with glioblastoma.